Delayed instabilities of water-retaining earth structures - Ubay-Anongphouth, Irene Olivia; Alfaro, Marolo (Frontiers in Built Environment, 2022)
Aging earth fill dams that were constructed in the mid-1950’s are beginning to show signs of instability associated with time-dependent degradation of shear strength. The strength degradation can be attributed to fissures, leaching of cementation, and creep in highly plastic clays, among other issues. The time-dependent processes are being examined in an earth fill dam that experienced slope instability but did not result in a loss of water. This paper discusses research findings on the mechanisms of delayed slope instability of an earth fill dam. Identifying the operating mechanisms of instability is useful in developing sound and practical remedial measures. It is also a useful way of being more proactive on the part of engineers in assessing the stability of dams at other generating stations that may not satisfy modern dam safety standards.